2008
DOI: 10.1097/inf.0b013e31816ff7c5
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Transmission of Mycobacterium Tuberculosis Among Children on a School Bus

Abstract: We report a tuberculosis outbreak in school children caused by exposure to a sputum-smear positive school bus driver. Exposed children were assessed using 2 versions of interferon-gamma release assays. Fifty-five percent (18/34) had a positive interferon-gamma release assays and 4 children developed tuberculosis. This suggests that transmission may be very efficient in this setting and highlights the need for early diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…The meta-analysis included cohort studies of children who were screened as part of an investigation of a tuberculosis outbreak,11 12 20 21 22 who were referred to hospital as close contacts of index cases,20 21 23 24 25 were household contacts of an infectious adult,13 26 27 28 or were contacts in other settings 29. Four studies were conducted in the United Kingdom, two each in the Gambia and Spain, and a single study in Greece, Italy, Indonesia, Turkey, South Africa, and Cambodia each (table) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analysis included cohort studies of children who were screened as part of an investigation of a tuberculosis outbreak,11 12 20 21 22 who were referred to hospital as close contacts of index cases,20 21 23 24 25 were household contacts of an infectious adult,13 26 27 28 or were contacts in other settings 29. Four studies were conducted in the United Kingdom, two each in the Gambia and Spain, and a single study in Greece, Italy, Indonesia, Turkey, South Africa, and Cambodia each (table) .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were conducted in the United Kingdom, two each in the Gambia and Spain, and a single study in Greece, Italy, Indonesia, Turkey, South Africa, and Cambodia each (table) . BCG vaccination status was assessed in included studies by one or a combination of BCG scar,12 13 22 23 24 25 26 27 29 30 confirmed medical records,11 12 21 30 and parental recall of vaccination 21…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore highly probable that the majority of infection occurs indoors, in buildings other than individual’s own homes. Individual outbreaks of M.tb infection have been linked to a wide range of settings, including public transport [ 8 , 9 ], schools [ 10 ], churches [ 11 , 12 ] and healthcare facilities [ 13 , 14 ]. These kinds of study provide some information on locations where transmission can occur, but as outbreak investigations are typically only undertaken when unusual patterns of disease are noticed, they give little insight into the types of location where transmission is most common.…”
Section: Introductionmentioning
confidence: 99%
“…TB outbreaks usually occur in people who live in a closed and crowded environment. TB outbreaks have occurred in refugees [10–12], correctional facility [13], long-term care facility [14], schools [15,16] and on a school bus [17] in other countries. TB outbreaks in schools have frequently been reported in China [2, 6, 18–20].…”
Section: Discussionmentioning
confidence: 99%